Political Aversion To a Multilateral Fiscal Rule: The Dynamic Commitment Problem in European Fiscal Governance - Matthias Bauer (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2013)
From a retrospective perspective, effective future fiscal cooperation in Europe is not likely to stand a chance. Focusing on the Stability and Growth Pact (SGP, the Pact), this paper studies the determinants of national policymakers' changing commitment to a multilateral fiscal rule, referred to as the 'dynamic commitment problem'. The empirical analysis sheds light on the economic and political economy factors that contribute to national policymakers' aversion to a multilateral fiscal rule in a monetary union that is not a political union. The underlying analysis is based on an event study including 147 statements of EU heads of government (the European Council) and members of the Economic and Financial Affairs Council (the EcoFin) over the period 2001 to 2008. All statements are either related to flexible interpretations of the SGP or calls for changing the rules of the framework, thus being an indicator of political non-commitment to the Pact. Standard political-economy theory is considered to derive a number of testable hypotheses. The unique dataset is linked to econometric analysis in order to estimate the effects of national economic and national political economy determinants on the strength of political aversion to the SGP. The empirical findings show that political aversion to the SGP is positively correlated to the national budgetary deficit, negatively correlated to domestic economic growth and negatively correlated to the costs of government borrowing. In addition, the results indicate that economic and political power, government fragmentation and rising non- commitment amongst other member countries' politicians systematically influence national political aversion to the SGP. The findings cast serious doubts on future EU/EMU policymakers' full commitment to the recently revised SGP and the recently adopted European Fiscal Compact, both of which are discussed in the final part of the paper.
urn:nbn:de:gbv:27-20131126-112407-0
Keywords: E62; F55; C22; C58; 330; fiscal rules; monetary union; political economy